Uma História para Contar: A formação em serviço de professoras alfabetizadoras - Macedo, Stella Maris Moura de (2004)
The purpose of this investigation is to relate some experience that has been held by a group of read and write teachers from Baixa do Sapateiro Cooperation Class Elementary School, a public municipal school placed in Maré District. These teachers’ process of formation at work is, therefore, the object of this dissertation. Thus, the school quotidian comes into prominence as a favoured setting for teachers’ dialogues and reflexions about their daily pedagogical pactices. In order to deeply understand how the knowledges build our teaching and learning development tissue, I should collect and report some stories of our own, read and write teachers. The investigation is theoretically placed in the qualitative methodology connected with the school quotidian. Since my intention is to show these teachers’ actions and reflexions, I aim to point out and proclaim the need to include our everyday production and creation in teaching school courses and programs. In this way, the dissertation comes to identify and study some significant elements from theory and practice. As a leading guide for this piece of work, the pedagogical practice may be considered the main element of this investigation.